2018
DOI: 10.1001/jamainternmed.2017.6313
|View full text |Cite|
|
Sign up to set email alerts
|

Care Planning for Inpatients Referred for Palliative Care Consultation

Abstract: IMPORTANCE Care planning is a critical function of palliative care teams, but the impact of advance care planning and goals of care discussions by palliative care teams has not been well characterized.OBJECTIVE To describe the population of patients referred to inpatient palliative care consultation teams for care planning, the needs identified by palliative care clinicians, the care planning activities that occur, and the results of these activities. DESIGN, SETTING, AND PARTICIPANTSThis was a prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
3
22
0
1
Order By: Relevance
“…Advance care planning was the most common reason for PC consultation (73.5%; range, 39.9%-97.4%) (Table 1), a finding discussed in more detail in previous work. 20…”
Section: Resultsmentioning
confidence: 99%
“…Advance care planning was the most common reason for PC consultation (73.5%; range, 39.9%-97.4%) (Table 1), a finding discussed in more detail in previous work. 20…”
Section: Resultsmentioning
confidence: 99%
“…For patients with POLST documents, this rate was higher. Medical record inaccuracy related to code status is not new and was effectively reported by Bischoff et al 19 Furthermore, previous research supports discordant rates (30%–50%) of what was documented on a POLST versus patient informed consent. 18…”
Section: Discussionmentioning
confidence: 62%
“…The result was creation of DNR orders or having changed full-code orders to DNR orders after interventions. 19 Additional research has been directed to study code status transition from full code to DNR. 20 These studies did not included patients with existing DNR orders or the reversal of DNR to Full Code Orders.…”
mentioning
confidence: 99%
“…Third, although we were able to follow our respondents over time in order to assess stability of preferences and the experiences of life-events, this study doesn’t provide data about the end of life of the participants. We know from a study by Bischoff et al that 37% of patients change their code status near the end of life [29]. On the other hand Bolt et al found that a change or deterioration in health near the end of life generally did not seem to influence preferences concerning euthanasia of people with an advance euthanasia directive [30].…”
Section: Discussionmentioning
confidence: 99%